2008
DOI: 10.1007/s11947-008-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Gelling Properties of Tyrosinase-Treated Dairy Proteins

Abstract: Protein-based viscous gels can augment or replace carbohydrate-based ones for specific nutritional formulations such as in reduced calorie or low-fat food applications. In this study, slurries of whey protein isolates and calcium caseinate mixed with alginic acid (20% T.S.) were subjected to high-shear homogenization (microparticulation) at 27,000 rpm for 2, 3, 4, and 6 min. The resulting slurries were incubated with mushroom tyrosinase (E.C. 1.14.18.1) at levels of 3, 6, and 9 mg/100 g for 15, 30, and 60 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Oxidation of tyrosine residues result in an increase in molar mass, steric hindrance of the protein molecules and a higher viscous aqueous solutions (Fargemand et al, 1998). Milk proteins treated by mushroom tyrosinase resulted in the dispersion a higher viscosity (Onwulata & Tomasula, 2010). Laccase, peroxidase (Fargemand et al, Fig.…”
Section: Functional Properties Of the Treated Caseinatesmentioning
confidence: 99%
“…Oxidation of tyrosine residues result in an increase in molar mass, steric hindrance of the protein molecules and a higher viscous aqueous solutions (Fargemand et al, 1998). Milk proteins treated by mushroom tyrosinase resulted in the dispersion a higher viscosity (Onwulata & Tomasula, 2010). Laccase, peroxidase (Fargemand et al, Fig.…”
Section: Functional Properties Of the Treated Caseinatesmentioning
confidence: 99%
“…Tyrosinases have been also investigated in dairy processing (Thalmann and Lötzbeyer, 2002;Onwulata and Tomasula, 2010;Ercili Cura et al, 2010) to improve the texture of products. However, due to the brownish color formation during the reactions, the applicability of tyrosinases in certain food applications may be limited (Martinez and Whitaker, 1995;McEvily et al, 1992;Falguera al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Selinheimo et al (2007a) showed that tyrosinase from P. sanguineus and T. reesei could cross-link a-casein while tyrosinase from A. bisporus and plant tyrosinases were able to create cross-links only in the presence of an auxiliary compound. Mushroom tyrosinase was reported to increase the viscosity of heatinduced milk protein gels prepared by addition of alginic acid and high-shear homogenization (Onwulata & Tomasula, 2008). Moreover, tyrosinases were also reported to induce formation of proteineoligosaccharide conjugates (Selinheimo, Lampila, Mattinen, & Buchert, 2008) and grafting of peptides onto polysaccharides (Aberg, Chen, Olumide, Raghavan, & Payne, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, enzymatic tailoring of the interactions between casein molecules is expected to alter the structural properties of the milk protein-based systems. To our knowledge, there are only a few reports (Ercili Cura et al, 2009;Onwulata & Tomasula, 2008;Steffensen, Andersen, Degn, & Nielsen, 2008) focused on the utilization of oxidative enzymes in structure modification of dairy systems. The aim of this work was to elucidate the gelation of milk proteins upon modification by two tyrosinases of different origin, i.e., T. reesei tyrosinase and A. bisporus tyrosinase.…”
Section: Introductionmentioning
confidence: 99%